Clinically Based Models of Teacher Preparation: A Snapshot of Three Systems - Dietrich, Sylvia L.; Hulan, Nancy; Kirby, Gail; Evans, Sam (Educational (Re)naissance, 2016)
A teacher preparation institution critically reviewed current programs and began moving toward a clinically based model. One focuses on Middle Grades/Secondary Math and Science, another focuses on Secondary English Language Arts, and a pilot project focuses on Elementary with a minor in either English/Language Arts or STEM (science, technology, engineering, and mathematics). Keywords: teacher education, clinical practice, and clinical teacher preparation